A Differentiated Approach to the Complex Treatment of Cornea Ulcers - E. V. Chentsova; E. N. Verigo; A. I. Hazamova (Oftalʹmologiâ, 2018)
Ulcerative lesions of the cornea in 17–21 % lead to functional and up to 8 % to anatomical death of the eye depending on the severity. The aim of the work was to develop an algorithm of surgical treatment of patients with corneal ulcers. Comprehensive examination, treatment and outcomes in the dynamics of ulcerative lesions was performed in 126 patients, 86 patients of them received surgical intervention (with the threat of corneal perforation or present) for emergency indications and in 40 cases combined treatment was carried out with the use of a crosslinking (CRL) in corneal ulcer and ulcer a corneal transplant. Surgical intervention included autoconjuctival plasty (AUC), the transplantation of amniotic membrane in combination with blepharorrhaphy (TAM + BR), lamellar keratoplasty (PKP), penetrating keratoplasty (PK), reconstructive keratoplasty (RCP). The most favorable outcomes with relief of inflammation were achieved in RCP and PC. In cases of delayed epithelialization of the cornea and graft (herpesvirus infection and trophic disorders), the most resonant ones were TAM and TAM + BR. CRL treatment was carried out in 3 variants: 1-as the main method of treatment, 2 — CRL in combination with TAM + BR, 3 — CRL + keratoplasty ( 5–7 days after surgery). As a treatment result, epithelialization of ulcerative-destructive process and partial increase in visual acuity were observed in all patients. Based on the results of patient’s treatment the algorithm of complex surgical care was created. It takes into account the etiology, localization, depth and severity of the inflammatory process, the area of ulcerative lesions of the cornea and of the graft, reduced terms of treatment inflammation and rehabilitation period.